Pengaruh Konsentrasi dari Gliserol Terhadap Plastik Biodegradable Berbahan Pati dari Kulit Singkong - Leni Widiarti; Sajaratud Dur; Aisyah Rafiqah Azla Siregar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Indonesia is the second-largest producer of plastic waste in the world, while conventional plastics require a long time to decompose and may generate harmful emissions. Therefore, the development of biodegradable bioplastics has become increasingly important. Abundant cassava peels have potential as a starch source, with glycerol serving as a plasticizer and chitosan as a reinforcing agent. This study aimed to analyze the effect of varying glycerol concentrations (0, 2, 4, 6, and 8 mL) on the functional group characteristics and thermal properties of cassava peel starch–chitosan-based bioplastics. The bioplastics were synthesized by blending starch and chitosan at an 8:2 ratio, followed by the addition of glycerol at different concentrations. Characterization was conducted using Fourier Transform Infrared (FTIR) spectroscopy and Differential Scanning Calorimetry (DSC). FTIR results indicated no formation of new functional groups; however, shifts and broadening of the –OH absorption bands were observed, suggesting physical interactions through hydrogen bonding among starch, chitosan, and glycerol. DSC analysis revealed that glycerol concentration significantly affected the thermal properties of the bioplastics, with the highest melting temperature (Tm) obtained at 6 mL glycerol (160.67 °C) and the lowest at 8 mL glycerol (129.33 °C). The formulation containing 8 mL glycerol exhibited the highest fusion enthalpy (321.73 J/g). These findings indicate that the addition of 6 mL glycerol provides the most optimal plasticization condition with the highest thermal stability, whereas higher glycerol concentrations result in over-plasticization. The optimal formulation shows potential for further development as an environmentally friendly packaging material.